Introduction to the density matrix renormalization group ansatz in quantum chemistry - Chan, Garnet Kin-Lic; Dorando, Jonathan J.; Ghosh, Debashree; Hachmann, Johannes; Neuscamman, Eric; Wang, Haitao; Yanai, Takeshi (Frontiers in Quantum Systems in Chemistry and Physics, 2008)
The Density Matrix Renormalisation Group (DMRG) is an electronic structure method that has recently been applied to ab-initio quantum chemistry. Even at this early stage, it has enabled the solution of many problems that would previously have been intractable with any other method, in particular, multireference problems with very large active spaces. Historically, the DMRG was not originally formulated from a wavefunction perspective, but rather in a Renormalisation Group (RG) language. However, it is now realised that a wavefunction view of the DMRG provides a more convenient, and in some cases more powerful, paradigm. Here we provide an expository introduction to the DMRG ansatz in the context of quantum chemistry.

Study of cumulant approximations to n-electron valence multireference perturbation theory - Zgid, Dominika; Ghosh, Debashree; Neuscamman, Eric; Chan, Garnet Kin-Lic (Journal of Chemical Physics, 2009)
We investigate the possibility of reducing the complexity of multireference perturbation theory through cumulant based approximations to the high-order density matrices that appear in such theories. Our test cases show that while the cumulant approximated forms are degraded in accuracy relative to the parent theory and exhibit intruder state problems that must be carefully handled, they may provide a route to a simple estimation of dynamic correlation when the parent perturbation theory is infeasible. Nonetheless, further work is clearly needed on better approximations to the denominators in the perturbation theory.